Electronic, Magnetic and Spin-polarized Transport Properties of the Zigzag-Zigzag Penta-graphene Nanoribbon - Tien, Nguyen Thanh; Tuan, Nguyen Thanh; Thao, Pham Thi Bich (Communications in Physics, 2021)
Electronic, magnetic and spin-polarized transport properties of the zigzag-zigzag pentagraphene nanoribbon are investigated theoretically within the framework of density functional theory combined with non-equilibrium Green’s function formalism. It is found that the spinunpolarized ZZ-PGNR behaves as metal. However, the spin-polarized ZZ-PGNRs show to be the magnetic semiconductor properties. More importantly, for the ZZ-PGNRs based device, the spin-filtering effect occurs strongly near Fermi level. Our findings suggest that ZZ-PGNRs might hold a significant promise for developing spintronic devices.